2000
DOI: 10.1111/j.1540-8159.2000.tb07043.x
|View full text |Cite
|
Sign up to set email alerts
|

Single Oral Administration of Pilsicainide Versus Infusion of Disopyramide for Termination of Paroxysmal Atrial Fibrillation: A Multicenter Trial

Abstract: A single oral dose of pilsicainide (PLS) is effective in terminating acute‐onset atrial fibrillation (AF). However, the effectiveness of this single oral treatment has not been compared with the infusion of other antiarrhythmic drugs. The effects of a single oral dose of PLS on the termination of AF were compared with an infusion of disopyramide (DISO) in a multicenter trial. Seventy‐two patients with electrocardiographically confirmed, symptomatic, paroxysmal AF (< 48‐hour duration) were randomized to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Furthermore, a single oral dose of pilsicainide (100-150 mg) had a similar conversion rate to that of intravenous disopyramide (2 mg/kg up to a maximum dose of 100 mg) in patients with recent-onset AF. 15 Okishige et al determined the efficacy of pilsicainide (50 mg t.i.d.) and placebo in patients with long-lasting AF (>6 months) in whom electrical cardioversion had been scheduled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a single oral dose of pilsicainide (100-150 mg) had a similar conversion rate to that of intravenous disopyramide (2 mg/kg up to a maximum dose of 100 mg) in patients with recent-onset AF. 15 Okishige et al determined the efficacy of pilsicainide (50 mg t.i.d.) and placebo in patients with long-lasting AF (>6 months) in whom electrical cardioversion had been scheduled.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Our previous study 16 showed that a 4-week oral treatment with pilsicainide terminated long-lasting (>6 months) AF in 21% of patients, which is a similar conversion rate to that of oral amiodarone in patients with persistent or chronic AF. 11 However, although conducted in a randomized and placebo-controlled fashion, the study had some drawbacks.…”
mentioning
confidence: 96%
“…12 Clinical studies have reported that this drug is highly effective at terminating AF. 13,14 In the dog, it has been reported that sodium-channel blocker suppresses focal discharges in the PV. 15,16 Moreover, in humans, Kumagai et al 17 demonstrated that pilsicainide prolonged the PV ERP and PV-LA conduction time and created pharmacological PV isolation just before the termination of AF because of the suppression of conductivity within the PVs and at the PV-LA junction.…”
Section: Effects Of Pilsicainide On Electrophysiological Properties Omentioning
confidence: 99%
“…After the assessment of the basal control state, the animals were randomly assigned to two groups; namely, pilsicainide-or saline-administered groups. Then, the therapeutic dose of 1 mg / kg of pilsicainide (n = 6) or a vehicle saline (n = 6) was administered in a volume of 1 ml / kg through the femoral vein (4,5). Effects on the PR interval, QRS width, and QT interval of the ECG, heart rate, mean blood pressure, and Af duration were assessed 10, 20, 30, and 60 min after the drug administration.…”
mentioning
confidence: 99%
“…In this report, we describe this new method, which can be completed within 10 min after the induction of anesthesia. Moreover, in order to test the model, we selected a pure sodium channel blocker pilsicainide, since in Japan, the drug has been most widely used against clinical paroxysmal Af attack (4,5).…”
mentioning
confidence: 99%